Аналіз методології IDEF для розвитку бізнес-процесів - Голуб, О. Ф. (ХНУРЕ, 2019)
An analysis of the IDEF methodology was conducted to develop business processes, their features and applications. The IDEF methodology is a family of functional modeling standards, a way to identify certain processes. Typically, the IDEF modeling (IDEF0, as can be found in many sources) is the first step in learning any system.
Keywords: IDEF methodology; business processes